Time-Inconsistent Preferences and Strategic Self-Control in Digital Content Consumption - Zhang, Shuo; Chan, Tat Y.; Luo, Xueming; Wang, Xiaoyi (Marketing Science, 2022)
This study examines consumers’ time-inconsistent preferences in digital content consumption and their strategic self-control behaviors.